Descriptive Study of Gadget Usage Patterns and Their Implications for Academic Performance and Health - Nur Inayah Rauf; Irwan Irwan; Anna Maria Daud; Anggun Dinianti (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
The widespread adoption of digital technologies among university students necessitates a thorough investigation into their usage patterns and the multifaceted implications for academic achievement and health. This study aims to provide a descriptive overview of gadget usage patterns among university students. This study utilizes a descriptive research design with a cross-sectional approach. A sample size of 77 students was selected using a consecutive sampling sampling technique. data collection was conducted using a questionnaire in the form of a Google form. This study found that the majority of respondents were female (53.2%), aged 18-23 years (54.5%), who used gadgets for 1-6 hours daily (53.2%). The most commonly used application was social media (27.3%). Smartphones and tablets were the gadgets used most frequently (57.1%), which the respondents kept near them while sleeping (41.6%). Within the home, the TV was located in the bedroom or near the bedroom (35.1%), and the respondents reported their emotional condition as normal (68.8%). Gadget usage among students is shaped by their characteristics and behavioral patterns in utilizing technology. Further research is needed to examine the implications of these usage patterns on students' academic achievement and well-being.